Measuring qualitative characteristics of internet financial reporting: Evidence from Malaysia - Nelson Lajuni; Mathew Kevin Bosi; Mohd Noor Azli bin Ali Khan; Melissa Della Joy (Macrothink Institute, 2024)
As the world economy undergoes a rapid digital transformation, Internet financial reporting (IFR) has evolved into an important platform for the dissemination of information to investors. It has also been a central topic of discussion among practitioners and researchers due to the lack of rigorous regulations to govern IFR practices, resulting in disclosures of financial reports varying across listed companies. This study aims to assess the level of compliance with the qualitative characteristics of IFR for companies listed on Bursa Malaysia. This study involves adopting 34 constructed index items based on prior literature and the use of a 5-point Likert scoring scale anchored from "very poor" (1) to "excellence" (5) to measure the fundamentals and enhance the qualitative characteristics of IFR, which is also in line with the "Revised Conceptual Framework for Financial Reporting" issued by the Malaysian Accounting Standards Board (MASB) in 2018. Non-probability purposive sampling was employed to select the companies from 11 relevant industries, comprising 160 listed companies from the main market of Bursa Malaysia. Annual reports and corporate governance statements were extracted from corporate websites for 2018. Findings suggest that most corporations that are listed in the main market of Bursa Malaysia have yet to fully comply with the MASB’s financial reporting framework, notably timeliness, which requires urgent improvement. Without strict IFR regulations, managers may also be free to act opportunistically by planning their IFR disclosure in a way that benefits both the company's reputation and their interests. This research enriches the body of literature on IFR and provides a measuring mechanism that can gauge the level of compliance with the qualitative characteristics of IFR. It acknowledges the importance of collective efforts from regulatory bodies to implement accounting reforms and the best IFR governance practices to harness information's usefulness in the Industrial Revolution era. 4.0.